The Intra-Group Baryons in the LEO I Pair From the VST Early-Type GAlaxy Survey - Ragusa, Rossella; Mirabile, Marco; Spavone, Marilena; Cantiello, Michele; Iodice, Enrichetta; La Marca, Antonio; Paolillo, Maurizio; Schipani, Pietro (Frontiers in Astronomy and Space Sciences, 2022)
In this paper we present the deep, wide-field and multi-band imaging of the LEO I pair NGC 3379-NGC 3384, from the VST Early-type GAlaxy Survey (VEGAS). The main goal of this study is to map the intra-group baryons in the pair, in the form of diffuse light and globular clusters (GCs). Taking advantage from the large covered area, which extends for ∼ 3.9 square degrees around the pair, and the long integration time, we can map the light distribution out to ∼ 63 kpc and down to ∼ 30 mag/arcsec2 in the g band and ∼ 29 mag/arcsec2 in the r band, deeper than previous data available for this target. The map of the intra-group light (IGL) presents two very faint (μg ∼ 28-29 mag/arcsec2) streams protruding from the brightest group member NGC 3379 and elongated toward North-West and South. We estimate that the fraction of the stellar halo around NGC 3379 plus the intra-group light is ∼17±2% in both g and r bands, with an average color g-r = 0.75 ± 0.04 mag. The color distribution of the GCs appears multi-modal, with two dominant peaks at (u-r) = 1.8 mag and (u-r) = 2.1 mag, respectively. The GC population stretches from North-East to South-West and from North-West to South of the pair, in the last case overlapping with the streams of IGL, as well as the PNe distribution found by Hartke et al. (Hartke et al., A&A, 2020, 642, A46) and Hartke et al. (Hartke et al., 2022). Since these structures are elongated in the direction of the two nearby galaxies M96 and NGC 3338, they could be the remnant of a past gravitational interactions with the pair.